1988
DOI: 10.1016/0014-5793(88)80133-9
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin stimulates delayed‐onset, Ca2+‐dependent catecholamine release and the ADP‐ribosylation of a 40 kDa protein in bovine adrenal chromaffin cells

Abstract: Pertussis toxin was found to stimulate catecholamine release from bovine adrenal chromaffin cells in a Cazf-dependent manner and in the absence of any stimulatory or inhibitory agonists for this cell. The release of catecholamine was associated with the ADP-ribosylation of an approx. 40 kDa protein present in the total membrane fraction. These results are consistent with the existence of an exocytosis-linked G-protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…We report for the first time that long-term (8 or 24 h) treatment of BAMC cells with pertussis toxin caused a pronounced concentration-and time-dependent increase in ME secretion. The results of our short-term (1 h) study are in agreement with the report by Broklehurst and Pollard [6] in that the effect of short-term pertussis toxin on catechol amine secretion was weak. However, in the present study we found that long-term stimu lation (8 or 24 h) of BAMC cells with pertussis toxin caused a pronounced stimulation of ME secretion, suggesting that pertussis toxin-sen sitive G proteins play an important role in the regulation of the long-term secretion of ME in BAMC cells.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We report for the first time that long-term (8 or 24 h) treatment of BAMC cells with pertussis toxin caused a pronounced concentration-and time-dependent increase in ME secretion. The results of our short-term (1 h) study are in agreement with the report by Broklehurst and Pollard [6] in that the effect of short-term pertussis toxin on catechol amine secretion was weak. However, in the present study we found that long-term stimu lation (8 or 24 h) of BAMC cells with pertussis toxin caused a pronounced stimulation of ME secretion, suggesting that pertussis toxin-sen sitive G proteins play an important role in the regulation of the long-term secretion of ME in BAMC cells.…”
Section: Discussionsupporting
confidence: 83%
“…Pertussis toxin-induced ADP-ribosylation of the 40-kDa protein in BAMC cells and catecholamine release are correlated [3,6], Thus the pronounced increase in ME secre tion by pertussis toxin after 8 and 24 h in our study could be due to ADP-ribosylation. In creases of secretion of ME induced by pertus sis toxin are probably not due to its toxic effect since the concentration of pertussis toxin used in the present study does not cause the release of endogenous lactate dehydroge nase, indicating that the cells remained intact during incubation with pertussis toxin [6], To find the mechanisms involved in per tussis toxin-induced responses, the interac tion of pertussis toxin with different second messenger systems was studied. Our results suggest that the influx of calcium is required for both the increased secretion of ME and the enhanced expression of proENK mRNA in duced by pertussis toxin.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Pertussis toxin stimulates CA release from cultured bovine chromaffin cells in the absence of any exoge-nous stimulatory or inhibitory agonists for this cell (Brocklehurst & Pollard, 1988). The effect of the toxin was only apparent after an approximately 2 hr time lag, although exposure times as short as 15 min were sufficient for the effect of the toxin to develop.…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratories have reported that pretreatment of chromaffin cells with pertussis toxin (PTX) enhances both basal secretion from those cells and secretion in response to secretagogues including acetylcholine, nicotine, muscarinic agonists, and elevated K+ (Tanaka et al, 1987;Brocklehurst and Pollard, 1988;Ohara-Imaizumi et al, 1988, 1990Sasakawa et al, 1988;O'Sullivan and Burgoyne, 1989;Bansal et al, 1990;Sontag et al, 1991). Although three G-protein substrates for PTX-catalyzed ADP ribosylation have been identified in chromaffin cells (Toutant et al, 1987), the mechanism by which PTX produces this secretion-enhancing effect is unclear.…”
mentioning
confidence: 99%